The Urgent Need for the Adoption of an European Convention on the Profession of Lawyer - Elena Cristina Savu (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
Lawyers play an essential role amongst professions as primary actors in the system of justice and so by their contribution to protecting the Rule of Law, ensuring access to justice for citizens and protecting fundamental rights and freedoms. In this respect, the profession of lawyercan come under considerable pressure from the executive and legislative powers, as well as from the judiciary or non-state actors. The continuing attacks on the role of lawyers since the Recommendation No. R(2000)21 of the Committee of Ministers to Member States on the freedom of exercise of the profession of lawyer was adopted, that have accelerated lately, emphasize that The European Convention on the Profession of Lawyer is urgently needed.